Functional Layers of Inverted Flexible Perovskite Solar Cells and Effective Technologies for Device Commercialization - Zhiyuan Xu; Qixin Zhuang; Yuqin Zhou; Shirong Lu; Xiaohui Wang; Wensi Cai; Zhigang Zang (Small Structures, 2023)
Perovskite solar cells (PSCs) are now one of the most promising solar cells due to advantages such as high‐power conversion efficiency (PCE), low cost, and ease of fabrication. Among PSCs, flexible perovskite solar cells (FPSCs) are lightweight and bendable, making them easier to transport and install than rigid PSCs, and hence can be used in wearable and portable electronics, space energy systems, multifunctional integrated buildings, unmanned systems, and other applications. Compared with regular n–i–p FPSCs, inverted p–i–n FPSCs possess advantages of reliable operational stability, reduced hysteresis effect, low‐temperature fabrication process, and strong potential for tandem devices. At present, the PCEs of single‐junction and tandem‐inverted FPSCs have reached 21.76% and 24.7%, respectively, indicating promising commercial applications. In this review, first, the developments of device functional layers including flexible substrates, flexible conductive electrodes, charge transport layers, and perovskite active layers in inverted FPSCs are elucidated and discussed thoroughly. Then, the technologies for accelerating commercialization of inverted FPSCs are summarized in detail. Finally, perspectives on the development and commercialization of inverted FPSCs are provided.